First clinical trial of a newly developed capsule endoscope with panoramic side view for small bowel: a pilot study - Friedrich, Kilian; Gehrke, Sven; Stremmel, Wolfgang; Sieg, Andreas (Journal of gastroenterology and hepatology, 2013)
Background and Study Aims Capsule endoscopy is the first-line diagnostic technique for the small bowel. However, the inability to visualize the duodenal papilla is an inherent limitation of this method. In the present study, we evaluated feasibility of a newly developed CapsoCam SV1 capsule. Patients and Methods This is a prospective dual center study of a newly developed video capsule CapsoCam SV1 from Capsovision, CA, providing panoramic 360° imaging. A high frequency of 20 frames occurs per second for the first 2 h and thereafter 12 frames/s, with a battery life of 15 h. We evaluated feasibility and completeness of small bowel examination together with secondary endpoints of duodenal papilla detection in 33 patients. Patients swallowed the capsules following colonoscopy or were prepared with 2 L of polyethylene glycol solution prior to the examination. All patients swallowed 20 mg of metoclopramide and 160 mg of simethicone 30 min before ingestion of the capsule. Results Thirty-one of the 33 patients' data could be evaluated. Small bowel examination was complete in all procedures. Mean time to pass the small bowel was 258 ± 136 min. Average small bowel cleanliness was 3.3 ± 0.5. In 71% of the patients, we identified the duodenal papilla. No adverse reaction in relation to the capsule examination was observed. Conclusions CapsoCam SV1 is a safe and efficient tool in small bowel examination. The duodenal papilla as the only landmark in small bowel is detected in more than 70% of the patients.
Gesehen am 07.06.2021